49 Glucagon-like peptide-1 protects against cardiac remodelling after myocardial infarction via specific actions on the extracellular matrix. Issue 20 (23rd September 2011) - Robinson, E; Cassidy, R S; McDermott, B J; Green, B D; Grieve, D J
Abstract : Glucagon-like peptide-1 (GLP-1) is an insulin-releasing hormone clinically-approved for glycaemic control in type 2 diabetes, which also has important cardiovascular actions. Several groups have shown that GLP-1 protects cardiomyocytes from acute ischaemic damage. Here, we investigated whether exendin-4, a stable GLP-1 mimetic, has beneficial effects on chronic cardiac remodelling following myocardial infarction (MI). Adult normoglycaemic C57BL/6J female mice (8–10 weeks) were subjected to coronary artery ligation or sham surgery and chronically-infused with exendin-4 (25 nmol/kg/day) or vehicle for 4 weeks (n‰¥18). Echocardiography indicated that exendin-4 protected against left ventricular (LV) systolic (ejection fraction: sham, 57.8±8.6 vs MI, 43.5%±6.5%, p<0.05; sham exendin-4, 55.0±7.9 vs MI exendin-4, 48.3%±9.7%) and diastolic dysfunction (E/A ratio: sham, 1.98±0.58 vs MI, 1.52±0.58, p<0.05; sham exendin-4, 1.86±0.44 vs MI exendin-4, 1.71±0.73) and attenuated LV chamber dilatation (end-diastolic diameter: sham, 6.8±2.3 vs MI, 12.8±5.8 mm, p<0.05; sham exendin-4, 7.1±2.0 vs MI exendin-4, 10.5±4.1 mm). Interestingly, exendin-4 had no effect on cardiac hypertrophy, as assessed by morphometry/histology but exerted specific actions on the extracellular matrix as indicated by attenuation of MI-induced increases in interstitial fibrosis (MI, 9.65±2.83 vs MI exendin-4, 4.73%±1.10%, p<0.05) and pro-fibrotic/inflammatory gene expression (TGF-β: sham, 1.05±0.35 vs MI, 1.59±0.56, p<0.05; sham exendin-4, 0.95±0.25 vs MI exendin-4, 1.11±0.36), together with elevated decreases in MMP-9 expression post-MI (control, 19±73 vs exendin-4, 158%±122%, p<0.05). These results indicate that GLP-1 protects the ischaemic heart against contractile dysfunction post-MI via differential actions on key components of the remodelling phenotype, which may support its use as a novel therapeutic strategy in this setting.